2019
DOI: 10.1183/13993003.02089-2018
|View full text |Cite
|
Sign up to set email alerts
|

The Tuberculosis Network European Trials group (TBnet) ERS Clinical Research Collaboration: addressing drug-resistant tuberculosis through European cooperation

Abstract: While the incidence of tuberculosis (TB) has fallen steadily within the European Union, the region has by far the highest estimated incidence of multidrug-resistant (MDR)-TB among TB patients [1, 2], which hampers the goal of the World Health Organization (WHO) of TB elimination in the region [3]. MDR-TB has the potential to be the most important infectious threat to European health over the coming decades, unless effective treatment can be found and relapses prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Given the high prevalence of cryptococcal meningitis in Botswana and results from other studies, 5 culturenegative cryptococcosis might be an important contributor to undiagnosed meningitis. Better characterisation of these poorly described populations is warranted to inform better management and improve mortality.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Given the high prevalence of cryptococcal meningitis in Botswana and results from other studies, 5 culturenegative cryptococcosis might be an important contributor to undiagnosed meningitis. Better characterisation of these poorly described populations is warranted to inform better management and improve mortality.…”
mentioning
confidence: 86%
“…Regional and multinational efforts have attempted to pool these data for generalisable information. 5 Known weaknesses in these data restrict the inferences that can be drawn from them; 6 however, these weaknesses are surmountable with investments in the quality of longitudinal data and building of cross-regional partnerships. Considering RCTs as the sole source of evidence on MDR-TB treatment will restrict the generation of valid, timely evidence.…”
Section: Value Of Observational Data For Multidrugresistant Tuberculosismentioning
confidence: 99%
“…A cohort evaluation conducted in a cohort of 380 patients with MDR-TB concluded that the inclusion of relapse-free survival was a better marker of cure than the current definition based on the bacteriologic status at the end of treatment [22]. A definition of cure and treatment failure was proposed by the Tuberculosis Network European Trials (TBnet) group [23], based on the presence or absence of a positive culture 6 months after treatment initiation and the presence or absence of relapse 1 year after treatment completion [24]. Another proposal, which was evaluated on a central African cohort of 1,006 patients, aimed to modify outcome criteria to be suitable for short-course treatment in low- and middle-income settings.…”
Section: Historical Development Of Treatment Outcome Definitionsmentioning
confidence: 99%
“…These have the aim of 1) promoting the exchange of research ideas among clinicians and affiliated scientists in Europe and/or globally; 2) building an infrastructure for prospective clinical research; 3) securing additional funding through national and European Union funding streams; and 4) facilitating the planning, implementation, evaluation and publication of clinical and translational studies at pan-European level and beyond. So far, there are currently 17 ongoing CRCs that cover eight major respiratory disease domains (airway diseases, interstitial lung diseases, pulmonary vascular diseases, sleep and breathing disorders, respiratory critical care, paediatric respiratory diseases, respiratory infections and thoracic oncology), all of them linked to one or more ERS assemblies [2][3][4][5][6][7][8][9][10][11][12]. CADSET, an acronym that stands for "Chronic Airway Diseases Early Stratification", is the latest addition to the list of ongoing CRCs (www.…”
Section: Introductionmentioning
confidence: 99%